Penerapan Pembelajaran Tipe Jigsaw Pada Mata Pelajaran Sejarah Untuk Meningkatkan Aktivitas Belajar Dan Hasil Belajar Siswa Kelas XI IPS 1 Di Sekolah Menengah Atas Negeri 1 Muaro Jambi - Novrita Suryani; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract:This study aim to improve students learning result andstudents learning activity in History studies fro students in class XIIPS 1 SMAN Negeri 1 Muaro Jambi in 2017/2018 academic year byimplementing the Jigsaw model. The data collected throughobservation, documentation and interview. The result of studydisplay that are: 1) the Jigsaw model is able to improve learningprocess; 2) student’s learning result improves from 64% to 71% incycle I and to 85% in cycle II; 3) the Jigsaw model drives studentswilling for learning; 4) the responsibility of students improve; 5) andthe learning history become fun and meaningful.